Kajian Etnobotani Tumbuhan Sarang Semut Sebagai Obat oleh Masyarakat di Provinsi Bengkulu - Safniyeti Safniyeti; Sulistijorini Sulistijorini; Tatik Chikmawati; Haris Maulani; Fadel Nugraha; Devi Eka Lestari (Universitas PGRI Silampari, 2024)
The purpose of this study was to determine the utilization and cultivation of myrmecophytes as medicine by the community in Bengkulu Province. The sampling of this research was conducted through interviews with 5 key informants and 50 respondents using purposive sampling method and direct observation in the field, literature study and documentation. The results of the interviews were then analyzed descriptively to determine the utilization and cultivation of myrmecophytes as medicine by the community in Bengkulu Province. The results showed that there are two species of myrmecophytes namely Hydnophytum formicarum and Myrmecodia tuberosa in Bengkulu Province. These myrmecophytes is utilized by the people of Serawai, Rejang, and Lembak tribes for various types of diseases such as headaches, diabetes, tumors, aches, joint pain, cancer, rheumatism, high blood pressure, jaundice, vaginal discharge, back pain, and hepatitis. The myrmecophytes is also commercialized by the community by chopping and drying. The community that uses myrmecophytes also cultivates the plant using traditional methods such as placing it in coconut fiber, giving it soil media, and hanging it on trees in the residents yards. Information about the ethnobotanical study of myrmecophytes is expected to be known by the community in Bengkulu Province at large so that this plant can be recognized as a medicinal plant and an alternative to traditional medicine.